S31. RELATIONSHIP BETWEEN TIMING OF RELAPSE AND PLASMA DRUG LEVELS FOLLOWING DISCONTINUATION OF CARIPRAZINE TREATMENT IN PATIENTS WITH SCHIZOPHRENIA. (9th April 2019) - Correll, Christoph U; Jain, Rakesh; Meyer, Jonathan; Periclou, Antonia; Carrothers, Timothy; Barabássy, Ágota; Patel, Mehul; Earley, Willie; Kershenstine, Mindy
Abstract: Background: Relapse prevention remains an important treatment goal in schizophrenia, and oral atypical antipsychotics (AAPs) with long half-lives may confer continued treatment effects in cases of partial adherence or after drug discontinuation. Cariprazine, an oral dopamine D3-preferring D3/D2 receptor partial agonist and serotonin 5-HT1A receptor partial agonist with a relatively long half-life, is approved for the treatment of schizophrenia in the US and Europe. Cariprazine forms 2 major metabolites, desmethyl cariprazine (DCAR) and didesmethyl-cariprazine (DDCAR), which are pharmacologically equipotent to cariprazine; half-lives are 2–4 days for cariprazine, 1–2 days for DCAR, and 1–3 weeks for DDCAR. Here, we conducted a post hoc analysis of published relapse prevention clinical studies to explore the timing of relapse following drug discontinuation and its relationship to predicted plasma levels. Methods: Data from a long-term, randomized, double-blind (DB), fixed-dose, placebo (PBO) controlled cariprazine relapse prevention study in patients with schizophrenia (NCT01412060) were analyzed. Patients were stabilized with cariprazine (3, 6, or 9 mg/day) during a 20-week, open-label phase, and eligible patients (eg, Positive and Negative Syndrome Scale [PANSS] total score ≤60, decrease from baseline ≥20% in PANSS total score) were randomized 1:1 to continue cariprazine or switch to PBO for up to 72 weeks of DB treatment. Relapse was defined by objective rating scale criteria, psychiatric hospitalization, and subjective clinical measures. Published studies of other oral AAPs with similar designs (e.g., stabilization phase ≥8 weeks, PBO-controlled) were used for comparison; elimination half-life of the other oral AAPs ranged from <1 day to approximately 4 days. Time to drug-PBO relapse separation and PBO relapse rates were estimated from Kaplan-Meier (K-M) curves. Separation was defined as a sustained difference of ≥5% incidence of relapse between the drug and PBO curves. Results: Cariprazine treatment was associated with significantly delayed time to relapse versus PBO (P=.0039, hazard ratio=0.52). The K-M curve for cariprazine showed a longer time to drug-PBO relapse separation of 6–7 weeks after randomization compared to the K-M curves for the other oral AAPs, which showed earlier separation at 1–4 weeks. This pattern was also reflected in PBO relapse rates at 4 weeks after last dose, which were 5% for cariprazine and ranged from 8% to 34% for other oral AAPs. At 2 and 4 weeks after last cariprazine dose, geometric mean values of model-predicted plasma concentrations for total CAR (sum of cariprazine, DCAR, and DDCAR) were 20.0 nM and 6.1 nM, respectively. Based on published EC50 estimates for D2 (13.0 nM) and D3 (3.8 nM) receptor occupancy by total CAR, these results suggest that D2/D3 receptors remain occupied 2–4 weeks after last dose. Elimination half-lives of other oral AAPs and their active metabolites (<1 day to ~4 days) suggest that plasma concentrations and D2/D3 receptor occupancy would be low or negligible at 2 and 4 weeks after last dose. Characteristics other than half-life, such as length of stabilization phase and type of drug discontinuation protocol, are likely not differentiating factors as they were relatively consistent across studies. Discussion: Discontinuation of cariprazine treatment appeared to be associated with a delayed incidence of schizophrenia relapse compared with other oral AAPs, which may be due to the longer half-life of cariprazine and its active metabolites. These results suggest that cariprazine may provide additional benefits for the prevention of schizophrenia relapse; prospective comparative trials are needed to confirm these results.